Effects of an Onion-Olive Oil Maceration Product Containing Essential Ingredients of the Mediterranean Diet on Blood Pressure and Blood Fluidity - Mayer, Beate; Kalus, Ulrich; Grigorov, Alexander; Pindur, Gerhard; Jung, Friedrich; Radtke, Hartmut; Bachmann, Knut; Mrowietz, Christof; Koscielny, Jürgen; Wenzel, Ernst; Kiesewetter, Holger (Arzneimittelforschung, 2001)
Twenty-four patients with arterial hypertension (WHO class I) received either 4 capsules of an onion-olive oil maceration product, containing essential ingredients of the Mediterranean diet, or placebo daily over a period of one week. In order to investigate the acute effect on arterial blood pressure, measurements were performed before and 5 h after the administration of the first dose of 4 capsules verum or placebo, respectively. For the evaluation of the long term effect further blood pressure measurements were performed after one week’s treatment with a daily dose of 4 capsules. After a wash-out phase of 2 weeks followed by a crossover, the second study phase, which was identical in design, was carried out. In addition patients were instructed to measure their blood pressure 4 times daily at home for the whole study period. Haemorheological parameters (platelet aggregation, erythrocyte aggregation, plasma viscosity and haematocrit) were also determined at the measuring points mentioned above. The onion-olive oil maceration product led to a significant decrease in systolic blood pressure. There was also a trend towards a decrease in diastolic blood pressure. The improved blood fluidity observed resulted from a decrease in haematocrit. All effects could be shown immediately and after one week’s administration
Keywords: Onion, arterial blood pressure, haematocrit, hypertension, phase II study, platelet aggregation